Analytical Aspects of Velocity Pulses on Seismic Behaviour of Mid-Rise Compound Skeleton of Steel Moment Frame and Eccentrically Braced Panels - Parsa Khazaei Rad (Iranian Society of Structrual Engineering (ISSE), 2019)
Steel moment frame and bracing panels compound structures are suitable systems for medium-height resistant skeletons due to their desirable ductility along with high rigidity when facing large dynamic forces caused by earthquakes. In this research, the seismic behavior of two 10-story buildings with compound systems of moment frame/eccentrically braced frames as well as moment frame/eccentrically braced frame with zipper elements are evaluated. The evaluation and changes of the seismic response parameters of the studied models are based on performing nonlinear time history analyses. The studied models are designed according to the fourth edition of seismic design provisions in Code 2800, plus the 6th and 10th issues of the Iranian National Building Regulations. Following the results of this research, it has been recognized that the existence of large coherent pulses in the time history of powerful earthquakes affects the response parameters of the building to a great extent. The results of this research includes the analytical process in the graphs related to maximum push of the drift, floors acceleration and velocity of the studied structural models and also the time history of story’s drift and axial force of the columns. The results show that seismic responses and demands under near-field records have a bigger appearance than the corresponding effects obtained exposed to far-field records.